Die opstanding van Jesus: God se nadergekome en steeds naderkomende protes en liefde - Veldsman, D. P. (Hervormde teologiese studies, 1993)
The resurrection of Jesus: The ever nearer coming God in protest and love The resurrection of Jesus poses the challenge to be understood from an historical as well as a systematictheological perspective. The one without the other give rise to very different and problematic shortcomings. Exploring this double-sided approach, the resurrection narratives - focussing firstly on the empty tomb - are related to the historic-archaeological possibility of a secondary burial of the body of Jesus by some of his disciples without the knowledge of the other. However, the appearances of Jesus are subsequently understood as God’s startling loving turn to history which, due to the very problematic interpretative nature of these appearances, have the character of invitation and not of proof. The appearances are understood from a systematic- theological line of interpretation, called ‘the ever nearer coming God in protest and love’.